2006
DOI: 10.1002/ps.1262
|View full text |Cite
|
Sign up to set email alerts
|

Variability in initial spray deposit in apple trees in space and time

Abstract: Variation in pesticide residues in space and time has not been investigated systematically in spite of the large variability found at single scales (e.g. between trees or orchards). Information on variability at different scales will support the development of sampling methods and more reliable prediction of residues. Experiments were conducted to quantify the spatiotemporal variability in initial spray deposit on apple leaves and fruit using a substitute tracer (zinc EDTA chelate). Five hierarchical spatial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 36 publications
6
38
2
Order By: Relevance
“…variation in initial deposit (Walklate et al 2003;Xu et al 2006), physical decay due to weather factors (Smith and MacHardy 1984) and growth dilution (Lakso et al 1995). The degradation of pesticide residues concentration due to the three processes has been approximately described by a first-order reaction model (Timme and Frehse 1980;Holland et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…variation in initial deposit (Walklate et al 2003;Xu et al 2006), physical decay due to weather factors (Smith and MacHardy 1984) and growth dilution (Lakso et al 1995). The degradation of pesticide residues concentration due to the three processes has been approximately described by a first-order reaction model (Timme and Frehse 1980;Holland et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the uptakes and accumulations of Cu in leaves or fruits are not only from the uptake of Cu from the soil but also from the deposit of Cu-containing fungicides (Özcan et al 2012). Many studies have shown that initial spray deposit and retention of pesticides are critically influenced by tree canopy structure (Travis et al 1987;Xu et al 2006;Rawn et al 2007). This variability would result in variation in differential interception of Cu deposit between zones among trees, leading to the significant observed zone-tree interactions.…”
Section: Copper Accumulations In Apple Leaves and Fruitsmentioning
confidence: 99%
“…3). The different enrichments of Cu in soils under different positions of the apple trees are apparently due to the different initial spray deposit of the different canopy compartments, which can result in different leaching effects through the drift, or dripping of excess sprays from leaf surfaces (Xu et al 2006;Rawn et al 2006).…”
Section: Copper Accumulations In Orchard Soilsmentioning
confidence: 99%
See 2 more Smart Citations